Penggunaan Media Sosial Terhadap Siswa Di Madrasah Aliyah Mualimin Makassar - Wahida Suddin; Sam’un Mukramin (KOLONI, 2023)
The development of the world at this time through the flow of globalization has given rise to new problems, including in the field of education, one of which is the use of social media which provides many conveniences that can be obtained from cellphones and the internet, almost all people as users of technology and information prove that at the moment This life cannot be separated from technology and information. This study aims to describe the use of social media among students of Mandarasa Aliyah Mualimin Makassar. The approach used by researchers is descriptive qualitative, data collection is done by interviews and observations. The subjects of this study were counseling teachers and two students of Madrasa Aliyah Mualimin Makassar. The results of the research found that social media influences teaching and learning activities in schools. Because teenagers have unstable characters, are selfish and prioritize fun, one way is to play social media, so they don't care about productive things and surfing the internet or playing positive social media. Awareness of social media and the internet in schools is a problem for teenagers or students in schools who have not been able to separate the truth.  Keywords: Social Media, Teenagers.